Effect of Heart Rate Variability Biofeedback Sessions With Resonant Frequency Breathing on Sleep: A Pilot Study Among Family Caregivers of Patients With Cancer - Hasuo, Hideaki; Kanbara, Kenji; Fukunaga, Mikihiko (Frontiers in Medicine, 2020)
Heart rate variability biofeedback (HRV-BF) is used as a skill in psychosomatic medicine, but is not yet established in the field of sleep. The present study aimed to evaluate the effect of HRV-BF with resonant frequency breathing (RFB) on sleep performed once every 2 weeks and the usefulness of practice of RFB using a portable device at home before bedtime. Participants were 69 family caregivers of patients with cancer that felt burdened by nursing care. We conducted a randomized controlled trial with an HRV-BF+Home practice group and an HRV-BF group. HRV-BF with RFB was administered to both groups at our medical institution for up to 30 minutes on the experiment days. Home practice involved RFB using a portable device, which was performed at home each day within 20 minutes before bedtime. Evaluation items were: change ratio of total score of the Pittsburgh Sleep Quality Index (PSQI) at 28 days after the trial started. In total, 52.2% of participants had insomnia. The two HRV-BF groups had decreased PSQI total scores, which indicated an improvement in PSQI total score near 5.5 on Day 28. The two HRV-BF groups had significantly increased HRV scores on Day 28, and there was correlation between the variation of PSQI total score and the variation of HRV score. The quality of sleep assessed by PSQI scores in the HRV-BF+Home practice group was significantly improved compared with the HRV-BF group on Day 28 (p = 0.001). This suggests HRV-BF may be a useful skill for enhancing sleep among family caregivers of patients with cancer, as well as supporting their autonomic nervous function. Additional actual regular practice of RFB (using a portable device at home before bedtime) may further enhance the effect.